2017
DOI: 10.9767/bcrec.12.3.951.430-436
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Concentration Ratio of TTiP:AcAc on the Photocatalytic Activity of TiO2 Thin Film in Reducing Degradation Products of Used Frying Oil

Abstract: The TiO2 thin film has been applied to reduce degradation products (free fatty acid/FFA and peroxide value/PV) in used frying oil under ultraviolet (UV) light irradiation. FFA and PV are degradation products in used frying oil that can cause various diseases in human. In this study, the TiO2 thin films were made from precursor solution with concentration ratio of titanium tetraisopropoxide (TTiP) and acetylacetone (AcAc) of 1:1, 1:2, 2:1, 2:3, and 3:2. The aim of this study is to investigate the effect of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, it is known that the TTIP:AcacH molar ratio 1:1 is not sufficient for complete complex formation; the complex is formed at the molar ratio of 1:2 and starting from the ratio 1:3 an excess of acetylacetone can be seen in the solution [16]. Few studies have focused on the effect of the TTIP:AcacH molar ratio on the structural properties [16] and photocatalytic activity of the films [28] and powders [29]. No comprehensive studies about addition of a high AcacH molar ratio into the precursor solution and its effects on the material and photocatalytic properties of the films were found in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that the TTIP:AcacH molar ratio 1:1 is not sufficient for complete complex formation; the complex is formed at the molar ratio of 1:2 and starting from the ratio 1:3 an excess of acetylacetone can be seen in the solution [16]. Few studies have focused on the effect of the TTIP:AcacH molar ratio on the structural properties [16] and photocatalytic activity of the films [28] and powders [29]. No comprehensive studies about addition of a high AcacH molar ratio into the precursor solution and its effects on the material and photocatalytic properties of the films were found in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of organic additives for the formation of anatase TiO 2 has been studied for many years, especially in relation to the preparation of nanoporous anatase matrixes for dye-sensitized solar cells and to photocatalysis . Stabilization of titanium­(IV) isopropoxide (TTIP) with acetylacetone (AcacH) and effects of AcacH on the film properties have been studied by several authors. Recently, it has been shown that the increase of the AcacH molar ratio in precursor solutions can increase the photocatalytic activity of the TiO 2 films . For example, a change of the TTIP: AcacH molar ratio from 1:4 to 1:8 resulted in an increase of the photodegradation reaction-rate constant under UV light by about a factor of 10 .…”
Section: Introductionmentioning
confidence: 99%